TREE SPECIES DIVERSITY IN PHRA THAT SI MUEANG PONG AREA, CHIANG MAI PROVINCE, THAILAND - Pongpan Leelahakriengkrai; Akharasit Bunsongthae; Audcharapat Insing (BIOTROPIA, 2024)
Article Highlights- Rich tree diversity found in Phra That Si Mueang Pong area. - Endangered species identified, promoting conservation efforts. - Unique plant distribution influenced by land use and water proximity. - Potential for ecotourism and environmental education in the region. - Study provides foundational data for future ecological research.AbstractThis research conducted a survey of perennial flora in ten subplots along the pathway leading to Phra That Si Mueang Pong, identifying a total of 30 species representing 20 families, 28 genera.  Dominant species included Lagerstroemia duperreana var. duperreana, Shorea siamensis, Pterocarpus macrocarpus, Tectona grandis, and Vitex canescens. Families with the highest species number were Fabaceae, Lamiaceae, Combretaceae, and Malvaceae. The study revealed the presence of both common and rare plant species in the area, with differences in species distribution between plots 1-5 and 6-10. Plots 6-10, near the Mae Tha Chang River, displayed higher biodiversity, correlating with the biodiversity index. The dominant species, based on the importance value index (IVI), were Pterocarpus macrocarpus, Lagerstroemia duperreana, Tectona grandis, Shorea siamensis, and Millettia brandisiana, respectively. Two species, Pterocarpus macrocarpus and Tectona grandis, were classified as endangered. The soil analysis indicated slightly acidic pH and relatively low moisture content, with significant differences between plots 1-5 and 6-10. The study suggests the potential for ecotourism and environmental learning centers in the Chiang Mai province cultural tourism destination, emphasizing the rich biodiversity and ecological value of the mixed deciduous and dry dipterocarp forest ecosystems.